Modern internet-technologies as a means of organization of collaborative learning of students of pedagogical specialties - Kyselyova, Olesia (My University, 2019)
The article highlights the actual problem of using Internet technologies in the process of collaborative learning of students of pedagogical specialties
Kyselyova О. B. Modern internet-technologies as a means of organization of collaborative learning of students of pedagogical specialties / О. B Kyselyova // Інноваційні педагогічні технології в цифровій школі : матеріали наук.-практ. конф. молодих учених (Харків, 15-16 травня 2019 р.) / за ред. Н.О. Пономарьової, О.А. Жерновникової. - Харків : Харків. нац. пед. ун-т ім. Г. С. Сковороди, 2019. – С. 22–23.
Keywords: Інтернет-технології, колаборативне навчання, освітній процес, вища школа; Internet technologies, collaborative learning, educational process, higher school